Implementasi Pembelajaran Virtual Dengan Pendekatan Andragogi Pada Mata Pelajaran Aqidah Akhlak Kelas IX Di Madrasah Tsanawiyah YKUI Sekargadung Dukun - Nisrina Watsiqah; Muyasaroh; Ladamay, Ode Moh. Man Arfa (Jurnal Mahasiswa Pendidikan, 2022)
Education in Indonesia is currently experiencing complex challenges. This is partly due to the fact that technology and communication have developed along with globalization, besides that it can have positive and negative impacts on a nation. Education as a part that is accustomed to globalization is seen as necessary to take credible and acceptable innovation steps. The development of science and technology has brought changes not only in learning materials, but also in the way of learning. virtual learning using an andragogic approach is education that has a focus on self-development for adults to be ready to even engage in their social roles. According to this background, the problem that can be defined is how to implement virtual learning with the andragogical approach and what are the supporting factors and obstacles to the class IX Aqidah Akhlak subject at MTs YKUI Sekargadung Dukun. MTs YKUI Sekargadung established the WhatsApp group and YouTube applications as a medium for conducting virtual learning, on the grounds that many students already have these applications and are economical in using quotas. The support in this implementation is flexible study time, while the obstacle experienced by most students is the weak internet network.